THE RELATIONSHIP BETWEEN THE COMPONENTS OF SPORTS TRAINING AND MAXIMIZING THE PERFORMANCE OF VOLLEYBALL PLAYERS AGED 15-16 YEARS - Andrieș Vasile; Onesim Florin (Editura Univeristatii "Stefan cel Mare" din Suceava, 2021)
In this paper we tried to highlight the close relationship between the components of sports training and performance. Using a very well developed, complex training plan, I tested a series of parameters. Following the final tests, it was proved that the methodology used paid off, that the means introduced in the training brought an important contribution to the performance capacity. From a statistical point of view, the experiment proved to be a success.